2018
DOI: 10.5435/jaaos-d-18-00076
|View full text |Cite
|
Sign up to set email alerts
|

Knee Pain After Intramedullary Nailing of Tibia Fractures: Prevalence, Etiology, and Treatment

Abstract: Intramedullary nailing is often the treatment of choice for fractures of the tibia, but postoperative knee pain is common after this procedure. Potential etiologies include implant prominence, injury to intra-articular structures, patellar tendon or fat pad injury, damage to the infrapatellar branch of the saphenous nerve, and altered biomechanics. Depending on the etiology, described treatment options include observation, implant removal, assessment and treatment of injured intra-articular structures, and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 35 publications
0
12
0
1
Order By: Relevance
“…However, MRI and arthroscopic assessment of the patellofemoral joint after SPN and IPN suggests minimal risk [ 5 , 14 ], and several anatomical studies show similar articular damage between approaches [ 83 85 ]. The influence of nail removal (if it occurs) should also be considered, as removal is always performed via an infrapatellar incision, regardless of the initial approach [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, MRI and arthroscopic assessment of the patellofemoral joint after SPN and IPN suggests minimal risk [ 5 , 14 ], and several anatomical studies show similar articular damage between approaches [ 83 85 ]. The influence of nail removal (if it occurs) should also be considered, as removal is always performed via an infrapatellar incision, regardless of the initial approach [ 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aetiology of AKP remains unclear [ 86 ], yet the choice of approach may play an important role: patients undergoing SPN may be more prone to loss of quadriceps function and damage to intra-articular structures; whereas IPN patients may suffer from increased likelihood of damage to the patellar tendon, fat pad, and saphenous nerve. A meta-analysis of 20 papers found an average of 47% of patients reported AKP at an average follow-up of 2 years, although how the AKP was assessed was not detailed in the review [ 87 ].…”
Section: Discussionmentioning
confidence: 99%
“…[3,6] Multiple etiologies of postoperative anterior knee pain exist, including implant prominence, injury to intra-articular structures, patellar tendon or fat pad injury, damage to the infrapatellar branch of the saphenous nerve, and altered biomechanics. [11] The suprapatellar approach avoids the branches of the saphenous nerve and also spares the patellar tendon, potentially lowering the risk for anterior knee pain. [2,14] Several studies have evaluated outcomes of anterior knee pain following SP and IP approaches.…”
Section: Anterior Knee Painmentioning
confidence: 99%
“…5 Causes of anterior knee pain following intramedullary interlocking nail include skin incision, injury to the intra-articular structures, size of tibial plateau and damage to the infrapatellar branch of the saphenous nerve. 6 Several studies in the literature have shown that the position of the proximal nail tip may be one of the causative factors of anterior knee pain after tibia nailing. One of the studies showed that anterior knee pain results due to anterior nail prominence of more than 5mm and superior prominence of nail closer to the tibial articular surface.…”
Section: Introductionmentioning
confidence: 99%